PENGARUH LATIHAN JUMP SHOT DAN BANK SHOT TERHADAP AKURASI FREE THROW PADA EKSTRAKURIKULER BASKET SMPN 4 SEMARANG - Ardiyansyah, M. Ilham; Royana, Ibnu Fatkhu; Zhannisa, Utvi Hinda (YLPK Mahardhika, 2025)
This study aims to determine the effect of jump shot and bank shot training on free-throw accuracy in the basketball extracurricular program at SMPN 4 Semarang. The research employed a quantitative experimental method using a pretest-posttest two-group design. The subjects consisted of 28 students who actively participated in the basketball extracurricular activity, divided into two treatment groups. The first group received jump shot training, while the second group received bank shot training. The instrument used was a free-throw accuracy test conducted over 10 trials, both before and after the training sessions. The data were analysed using a paired sample t-test, which yielded a significance value of 0.000 (< 0.05). This indicates that the null hypothesis is rejected and the alternative hypothesis is accepted. It can be concluded that there is a significant influence of jump shot and bank shot training on improving students’ free-throw accuracy. These types of structured shooting drills are recommended as part of regular training programs to enhance the basic basketball skills of school-level players.